Penggunaan Media Virtual pada Pembelajaran Bahasa dan Sastra Indonesia di Era Kelimpahan - Purlilaiceu Purlilaiceu (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
Entering the current era of abundance, all sectors, especially the education sector, are experiencing significant demands and changes. This is also based on the policy of implementing education during the Covid-19 pandemic emergency, so learning from home through distance or online learning is the main choice. As educators in this era, they are required to be more skilled and innovative in implementing online learning and being able to integrate learning with information and communication technology (ICT) in accordance with the criteria of 21st century teachers. This study aims to determine the utilization or effectiveness of using online-based virtual media on Indonesian Language and Literature learning. The method used in this research is descriptive quantitative. The data collection is done through an online questionnaire or questionnaire using google form. The research subjects were Indonesian language teachers and students at SMAN Cahaya Madani Banten Boarding School (CMBBS). The sampling technique in this study used the "Stratified random sampling" technique or stratified random sampling based on a certain level. Based on the research results, the authors conclude that the use of virtual online media is very effective and helps the learning process at SMAN CMBBS and this can certainly answer the challenges in an era of abundance.